Upaya Meningkatkan Kemampuan Guru dalam Menyusun Soal Penilaian Harian Bentuk Pilihan Ganda pada Guru SD Negeri 01 Krompeng Kecamatan Talun Kabupaten Pekalongan Melalui Kegiatan In House Training berbasis Sekolah - Zaenudin Zaenudin (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The aim of this study was to determine the increase in the ability of teachers at SD Negeri 01 Krompeng, Talun District, Pekalongan Regency, through School-based In House Training Activities in preparing daily assessment questions in the form of multiple choice. The method used in this research is the school action research method, data collection that is carried out through training, observation, and documentation studies. The results showed an increase in the ability of teachers in preparing daily assessment questions in the form of multiple choice. This is shown by 84% of the 70 daily assessment test items in the form of multiple choice made by the teacher in accordance with the criteria.